Effectiveness of Moringa Leaf Juice in Increasing Hemoglobin Levels and Reducing Blood Pressure in Pregnant Women with Anemia and Hypertension - Usman, Hastuti; Silfia, Niluh Nita; Narmin, Narmin; Dewie, Artika (YCAB Publisher, 2025)
Background: Anemia and hypertension during pregnancy are significant public health challenges, particularly in developing countries, as they are associated with increased risks of maternal and fetal complications, such as preeclampsia and stunting. Moringa (Moringa oleifera) leaves have been identified as a promising nutritional intervention due to their high iron and antioxidant content, which may contribute to improved hemoglobin levels and reduced blood pressure. Objective: This study aims to evaluate the effectiveness of Moringa leaf juice in enhancing hemoglobin levels and reducing blood pressure among pregnant women with anemia and hypertension. Methods: This research employed an experimental one-group pretest-posttest design. A total of 48 pregnant women with anemia and hypertension in the Aglomerasi region of Palu were selected using consecutive sampling. The study was conducted from January to April 2024 in Guntarano Village and Bale Village, Donggala Regency, as well as South Tinggede Village, Sigi Regency. Data analysis was performed using paired t-tests. Results: The findings revealed a significant increase in mean hemoglobin levels, from 9.77 g/dL to 10.25 g/dL (p < 0.001). Similarly, systolic blood pressure showed a significant reduction, decreasing from 141.72 mmHg to 131.52 mmHg (p < 0.001), while diastolic blood pressure also declined significantly, from 91.12 mmHg to 86.30 mmHg (p < 0.001). Conclusion: Moringa leaf juice is effective in increasing hemoglobin levels and reducing both systolic and diastolic blood pressure in pregnant women with anemia and hypertension. It is recommended that Moringa juice be considered as an alternative nutritional intervention to improve maternal health outcomes, particularly in resource-limited settings. Keywords:Moringa; oleifera; Hemoglobin; blood pressure